The Influence of Features, Services, Discount, and Promo-tions on the Go Food Application Toward the Sales of Soto Ayam Culinary Smes in Surakarta - P.F, Semana Vidia Valva; Dewi, Adhita Maharani (Sean Institute, 2025)
The development of technology is increasingly advancing, as seen in the growing popularity of the Go-Food application among the public. This presents a significant opportunity for culinary business owners, including small and medium enterprises (SMEs) specializing in soto ayam in Surakarta. This study aims to examine the extent to which service features, discounts, and promotions on the Go-Food application influence the sales of soto ayam SMEs in Surakarta. The research employs a quantitative method with a total of 40 respondents selected using purposive sampling. The respondents are consumers who have sold soto ayam through the Go-Food application. Data were collected using an online questionnaire. The findings indicate that the promotion feature has a partial effect on sales, whereas service features and discounts do not have a partial effect. However, all three variables collectively influence the sales of soto ayam through the Go-Food application in Surakarta. These findings highlight the importance of appropriate marketing strategies to enhance SME culinary sales in the digital era.